2020
DOI: 10.1016/j.oregeorev.2020.103648
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting fluid behavior during two styles of greisen alteration leading to distinct wolframite mineralizations: The Echassières district (Massif Central, France)

Abstract:  Fluid cooling, without evidence of sharp pressure variations, is the main cause for one wolframite mineralization episode.  Fluid flashing (vaporization), triggered by fracture-induced pressure drops, initiated crystallization of a second type of wolframite mineralization.  Greisenization of the Beauvoir granite is a continuous process (ca. 400°C down to 190°C), occurring at high temperature as pervasive alteration of the granite body, while at lower temperature it is localized to a vein system.  Globally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 80 publications
(126 reference statements)
2
23
0
Order By: Relevance
“…Multistage formation of W-mineralization (wolframite) from discrete hydrothermal episodes has been documented at the La Bosse stockwork in the Echassieres District of the Massif Central, France [49,50]. The Sisson Brook deposit may represent a similar case given the protracted magmatic and hydrothermal activity present in the area (ca.…”
Section: Scheelite Versus Wolframite Saturationmentioning
confidence: 99%
“…Multistage formation of W-mineralization (wolframite) from discrete hydrothermal episodes has been documented at the La Bosse stockwork in the Echassieres District of the Massif Central, France [49,50]. The Sisson Brook deposit may represent a similar case given the protracted magmatic and hydrothermal activity present in the area (ca.…”
Section: Scheelite Versus Wolframite Saturationmentioning
confidence: 99%
“…Collection samples from Bournac are part of a batch collected for the studies of Munoz and Moëlo (1982) and Munoz and Shepherd (1987). Finally, quartz veins from Nades and Pouzol-Servant districts were sampled on outcrop during the autumn 2016 and 2017, respectively (Monnier et al, 2018;Monnier et al, 2020). Samples from La Lucette, which were taken from different parts on the main mineralized vein, come from the rock collection of the French Geological Survey (BRGM).…”
Section: Sampling Strategy and Preparationmentioning
confidence: 99%
“…We have seen above how the five districts studied display different quartz trace-element signatures, including the two neighbour districts in the Sioule Nappe, Pouzol-Servant and Nades. Monnier et al (2018Monnier et al ( , 2019Monnier et al ( , 2020 have shown that greisen alteration of the Beauvoir granite developed a regionalscale fluid circulation that gave rise to distal mineralizations, among which is the Nades district. A particular aspect of the latter is that it was the only site showing Sb mineralization, although quartz from all manifestation of the greisen event(s) at Beauvoir showed Sb enrichment in their traceelements signatures.…”
Section: Deciphering Polyphase Sb Events the Case Of The Sioule Nappementioning
confidence: 99%
See 1 more Smart Citation
“…Addition of non-polar molecules such as N2, CO2, and CH4 yields a decrease of W concentration in solution (Dubessy et al, 1989;Gibert et al, 1992). Precipitation of wolframite at Puy-les-Vignes could have been triggered by several processes including cooling, depressurization, fluid mixing, and fluid-rock interaction (Heinrich et al, 1990;Wei et al, 2012;Dewaele et al, 2016;Chicharro et al, 2016;Lecumberri-Sanchez et al, 2017;Legros et al, 2019Legros et al, , 2020Monnier et al, 2020). In particular, fluid pressure drop induced by hydrofracturing of the host rocks results in significant decrease of CO2 solubility and pH increase, which can cause in turn wolframite precipitation (Liu et al, 2017).…”
Section: Hydrothermal Fluid Origin and Wolframite Precipitationmentioning
confidence: 99%